Heat Treatment of Steels - Di Schino, Andrea; Testani, Claudio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Steels represent a quite interesting material family, both from scientific and commercial points of view, following many applications they can be devoted to. Following this, it is therefore essential to deeply understand the relations between properties and microstructure and how to drive them via a specific process. Despite their diffusion as a consolidated material, many research fields are active regarding new applications. In this framework, in particular, the role of heat treatments in obtaining complex microstructures is still quite an open matter, which is also thanks to the design of innovative heat treatments.This Special Issue embraces interdisciplinary work covering physical metallurgy and processes, reporting on experimental and theoretical progress concerning microstructural evolution during the heat treatment of steels.